Common and country specific economic uncertainty - Haroon Mumtaz; Konstantinos Theodoridis (Queen Mary University of London, School of Economics and Finance, 2015)
We use a factor model with stochastic volatility to decompose the time-varying variance of Macro economic and Financial variables into contributions from country-specific uncertainty and uncertainty common to all countries. We find that the common component plays an important role in driving the time-varying volatility of nominal and financial variables. The cross-country co-movement in volatility of real and financial variables has increased over time with the common component becoming more important over the last decade. Simulations from a two-country DSGE model featuring Epstein Zin preferences suggest that increased globalisation and trade openness may be the driving force behind the increased cross-country correlation in volatility.
Keywords: C15; C32; E32; 330; FAVAR; Stochastic Volatility; Uncertainty Shocks; DSGE Model